Rationale and design of the HOVON 170 DLBCL-ANTICIPATE trial: preventing anthracycline-induced cardiac dysfunction with dexrazoxane - Marijke Linschoten; Jesse Geels; Erik van Werkhoven; Heleen Visser-Wisselaar; Martine E. D. Chamuleau; Arco J. Teske; Lourens Robbers; Simone Oerlemans; Heleen Crommelin; Marleen Breems-de Ridder; Astrid Schut; Folkert W. Asselbergs; et al. (Cardio-Oncology)
Abstract Background Dexrazoxane has been studied for its ability to prevent anthracycline-induced cardiac dysfunction (AICD) in several trials but its use in clinical practice remains limited. This is related to the low to moderate quality of the generated evidence, safety concerns and restricted prescribing indications. Additional randomized trials are needed before this drug can be routinely integrated into cardio-oncology clinical practice. Objectives To describe the rationale and design of the HOVON 170 DLBCL – ANTICIPATE trial. This trial aims to establish the efficacy and safety of dexrazoxane for the primary prevention of AICD in patients diagnosed with Diffuse Large B-Cell Lymphoma (DLBCL) treated with six cycles R-CHOP21 chemo-immunotherapy. Methods This is a multicenter, parallel-group, open-label, phase III trial, randomizing 324 patients between either no cardioprotective treatment or dexrazoxane from the first R-CHOP cycle. The primary and co-primary endpoints are the incidence of AICD within 12 months of registration and the percentage of patients with complete metabolic remission at the end-of-treatment PET-CT respectively. The trial is registered at the EU Clinical Trials Register (EU-CT number 2023-505377-32) and ClinicalTrials.gov (NCT06220032). Results The medical research ethics committee approved the trial in May 2024. Recruitment has started in September 2024 and is expected to last for three years. Conclusions This trial is poised to contribute crucial evidence concerning the efficacy and safety on the use of dexrazoxane in the primary prevention of AICD. The trial is anticipated to address critical knowledge gaps and offer important insights into the value of dexrazoxane in cardio-oncology practice.